Rubus fruticosus (blackberry) use as an herbal medicine - Verma, Rameshwar; Gangrade, Tushar; Punasiya, Rakesh; Ghulaxe, Chetan (Pharmacognosy Reviews)
Wild grown European blackberry Rubus fruticosus) plants are widespread in different parts of northern countries and have been extensively used in herbal medicine. The result show that European blackberry plants are used for herbal medicinal purpose such as antimicrobial, anticancer, antidysentery, antidiabetic, antidiarrheal, and also good antioxidant. Blackberry plant (R. fruticosus) contains tannins, gallic acid, villosin, and iron; fruit contains vitamin C, niacin (nicotinic acid), pectin, sugars, and anthocyanins and also contains of berries albumin, citric acid, malic acid, and pectin. Some selected physicochemical characteristics such as berry weight, protein, pH, total acidity, soluble solid, reducing sugar, vitamin C, total antioxidant capacity, antimicrobial screening of fruit, leaves, root, and stem of R. fruticosus, and total anthocyanins of four preselected wild grown European blackberry (R. fruticosus) fruits are investigated. Significant differences on most of the chemical content detect among the medicinal use. The highest protein content (2%), the genotypes with the antioxidant activity of standard butylated hydroxyanisole (BHA) studies 85.07%. Different cultivars grown in same location consistently show differences in antioxidant capacity.
Keywords: Anticancer; antidiabetic; antidysentery; antimicrobial; antioxidant; blackberry; phototherapeutics; R. fruticosus; rosaceae